(3HgLI GdfahS hGdCNdGb ajeG JejR Hg Gdbhe ef GdBOGH hGdCNdGbs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3hHYO agPG cJGH fajS aj HjGf fHPI UGdMI ef CNdGb GdYdeGA GdYGedjf GdPjf COQcfGge ChGFd GdfUa GdChd ef GdbQf GdYGTQ GdeTehf HGdUhajI s
(3BNQgG (B:s
(3hHYVge MaX eGajgG ef GdoefGbTGJ aEjGce ef eKd Pdc Ke EjGc hGdMeO ddg QH GdYGdejf hdjcf Pdc BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha (B39) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs